ANALISIS MINAT BELAJAR BAGI SISWA BOARDING SCHOOL DI MASA PANDEMI DALAM MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP UNGGULAN ALHIDAYAT LASEM - Moh Sholihuddin; Farida Isroani (Jurnal Bahastra, 2020)
The pandemic period is a condition where there is a certain number of diseases or groups so that the government enforces an online teaching and learning process. Online learning is a condition where students learn from home without teacher supervision so that the teaching and learning process is different from before. This study discusses how to learn Islamic religious education subjects and how to analyze interest in learning at SMP Unggulan Al Hidayat Lasem during the pandemic. This type of research is field research that uses quantitative methods with simple linear regression statistical analysis techniques. The results showed that students' interest in learning in PAI subjects showed a positive regression coefficient value, so it can be said that interest in learning had an effect on students' Islamic education lessons. So it was concluded that, student learning interest during the pandemic in Islamic education subjects at SMP Lasem  there was a decrease in interest in learning during the pandemic.